Diuron environmental levels effects on marine nematodes: Assessment of ecological indices, taxonomic diversity, and functional traits. (January 2022) - Hannachi, Amel; Nasri, Ahmed; Allouche, Mohamed; Aydi, Abdelwaheb; Mezni, Amine; D'Agostino, Fabio; Avellone, Giuseppe; Gambi, Crsitina; Beyrem, Hamouda; Mahmoudi, Ezzeddine
Abstract: Coastal marine systems are the most sensitive zones to emerging pollutants. The present study aims to investigate the effect of Diuron on the meiofaunal assemblages, collected from the Bizerte channel (Tunisia). Microcosm experiments were set up using four increasing Diuron concentrations [D1 (10 ng g −1 dry weight (DW)), D2 (50 ng g −1 DW), D3 (250 ng g −1 DW) and (1250 ng g −1 DW)] compared to non-contaminated sediments (controls) and all plots were incubated for 30 days. Our results show that Diuron-supplemented sediments provoked the significant decrease of meiofaunal abundance as well as a change in nematodes' diversity and structure composition. All univariate indices, as well as the cumulative k -dominance, were lower in the Diuron than the control plot. Additionally, the ordination of treatments according to the two-dimensional nMDS plots analysis showed a clear structural separation of the Diuron treated replicates from the controls based on the functional groups lists. These current data emphasize the utility of the use of biological traits in the detection of disturbances in the aquatic biotope. Graphical abstract: Image 1 Highlights: Diuron decreased meiofauna taxa abundance. Diuron modified nematodes ecological indices and taxonomic diversity. Diuron accumulated in sediment and changed nematode functional diversity. Feeding group was the most modified biological trait after Diuron exposure.